תן f (x) = x + 8 ו- g (x) = x ^ 2 - 6x - 7 איך אתה מוצא f (g (2))?

תן f (x) = x + 8 ו- g (x) = x ^ 2 - 6x - 7 איך אתה מוצא f (g (2))?
Anonim

תשובה:

ראה את כל תהליך הפתרון הבא:

הסבר:

ראשית, להעריך #g (2) # על ידי החלפה #color (אדום) (2) # עבור כל התרחשות של #color (אדום) (x) # בפונקציה #g (x) #:

# צבע (אדום) (x)) = צבע (אדום) (x) ^ 2 - 6 צבע (אדום) (x) - 7 # הופ post

# צבע (אדום) (2)) = צבע (אדום) (2) ^ 2 - (6 xx צבע (אדום) (2)) - 7 #

#g (צבע (אדום) (2)) = 4 - 12 - 7 #

#g (צבע (אדום) (2)) = -15 #

עכשיו אנחנו יכולים להחליף #color (כחול) (g (2)) # אשר #color (כחול) (- 15) # עבור כל התרחשות של #color (כחול) (x) # בפונקציה #f (x) #:

#f (צבע (כחול) (x)) = צבע (כחול) (x) + 8 # הופ post

#f (צבע כחול) (- 15)) = צבע (כחול) (- 15) + 8 #

#f (צבע (כחול) (- 15)) = -7 #

לכן, #f (g (2)) = -7 #